2012
DOI: 10.1159/000346279
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Disease Risk Factors among a New Zealand Cohort

Abstract: Background: Prostate cancer is a leading public health burden worldwide, and in New Zealand it is the most commonly registered cancer and the third leading cause of cancer deaths among males. Genetic variability and its associations with diet, demographic and lifestyle factors could influence the risk of this disease. Methods: The single nucleotide polymorphisms (SNPs) within a group of antioxidant genes and related markers were tested between patient and control cohorts, adjusted for significant differences b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 97 publications
1
59
0
Order By: Relevance
“…Geybels et al (2015) suggested that CAT gene polymorphism is associated with stage III/IV prostate cancers. In addition, Karunasinghe et al (2012) found a significant association between the C-262T allele and increased risk to PCa. In accordance with these results, Tefik et al (2013) found that CAT C-262T polymorphism is associated with increased risk to PCa.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Geybels et al (2015) suggested that CAT gene polymorphism is associated with stage III/IV prostate cancers. In addition, Karunasinghe et al (2012) found a significant association between the C-262T allele and increased risk to PCa. In accordance with these results, Tefik et al (2013) found that CAT C-262T polymorphism is associated with increased risk to PCa.…”
Section: Discussionmentioning
confidence: 93%
“…The activity of CAT, which is an essential antioxidant, was found to be significantly diminished in PCa patients. There are conflicting results in the literature regarding the role of the CAT (C-262T) gene polymorphism in PCa (Choi et al, 2007;Battisti et al, 2011;Karunasinghe et al, 2012;Tefik et al, 2013;Geybels et al, 2015;Hu et al, 2015). Geybels et al (2015) suggested that CAT gene polymorphism is associated with stage III/IV prostate cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, changes in the Sep15 structure promoted the experimental carcinogenesis in the mammary gland in mice [21,22]. However, as shown in Table 3, the described link between Sep15 Hu [16] Breast 60 African-American (USA) Increased cancer risk in CG/CG homozygotes Hu [16] Head and neck 33 African-American (USA) Decreased risk in CG/TA heterozygotes Hu [16] Head and neck 94 Caucasian (USA) No association Hu [16] Chronic myelogenous leukemia No association for SEP15 alone; two-loci interaction between SEPP1 and SEP15 3′-UTR polymorphisms and cancer susceptibility is not obvious [11,16,[23][24][25][26][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Karunasinghe et al reported an interesting finding in a New Zealand cohort with predominant European ancestry. The TT genotype at the 811 position of the 3′-UTR of the Sep15 gene was significantly overrepresented (11.5 %) in patients with benign prostate hyperplasia as compared either to healthy controls (3.5 %) or to patients with prostate cancer (5.4 %) [25]. In the seminal study of Hu et al [16], a significant association between the Sep15 811T allele variant and elevated breast cancer risk in African-American women was observed.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation